An experimental parametric study on the liquefaction resistance of sands in spreader dumps of lignite opencast mines. Issue 122 (July 2019) - Wichtmann, T.; Steller, K.; Triantafyllidis, T.; Back, M.; Dahmen, D.
Abstract: The results of a parametric study on the liquefaction resistance of sands dumped with spreaders in lignite opencast mines using undrained cyclic triaxial tests is presented. Undisturbed samples taken by ground freezing and disturbed samples of the same material reconstituted by different methods were compared. Based on this comparison, a suitable sample preparation method was chosen which reproduces the depositional process in the dumps and leads to a similar initial fabric and thus a similar behaviour under undrained cyclic loading. Numerous tests on more than 50 sands from the dumps or the excavation sites of the mines demonstrated a decrease of the liquefaction resistance with increasing content of plastic fines and with decreasing mean grain size, while no clear trend with uniformity coefficient was observed in the data for a constant relative density. The dependence of the liquefaction resistance on the initial values of mean effective stress and stress ratio is discussed based on respective test series. Furthermore, the increase of the undrained cyclic strength with decreasing degree of saturation and an enhancement caused by a drained monotonic or vibrational preloading is demonstrated. Based on tests with different sample sizes, membrane penetration effects were found to be negligible. Abstract : Highlights: Preparation by free fall or moist tamping reproduces fabric of sands in dumps. Reconstituted and undisturbed samples (ground freezing) show similar resistance. Liquefaction resistance decreases with fines content and grows with grain size. Influence of stress anisotropy on number of cycles to failure is moderate. Liquefaction resistance is increased by monotonic and cyclic preloading.